Pengaruh Current Ratio, Return on Equity, Debt to Equity Ratio dan Ukuran Perusahaan terhadap Price Book Value - Witri Aryani; Mia Laksmiwati (Studi Akuntansi, Keuangan, dan Manajemen, 2021)
Purpose: This study aimed to determine the effect of CR, ROE, DER and Company Size on PBV of Public Companies in Chemical Sub Sector Listed on the Indonesia Stock Exchange Period 2013-2017. Research Methodology: The sampling technique used was a purposive sampling method. The researched population was 11 companies and the samples used were 8 Public Chemical Sub Sector Companies Listed on the Indonesia Stock Exchange. The data used was multiple linear regression analysis, tested using the Statistical Package for the Social Science (SPSS) and Microsoft Excel 2016. In addition, the data used were secondary data in the form of complete financial statements during the 2013-2017 period. Results: The study results indicate that the DER variable has a positive and significant effect on PBV. Company Size has a positive and significant effect on PBV. In contrast, the CR and ROE variable do not affect the PBV.